Study guides

☆☆

Q: 6x plus 13 equals -2x - 19?

Write your answer...

Submit

Still have questions?

Related questions

4+2x-2x+1=13+6 Combine like terms. (4+1=5; 2x-2x=0; 13+6=19) 5=19 This problem has no solution.

(4 + 2x) - (-2x + 1) = 13 + 6 4 + 2x + 2x -1 = 19 4x +3 = 19 4x = 19 - 3 4x = 16 therefore x = 16/4 x = 4

2x + 5 = 13 2x = 8 x = 4

The answer to 1 over 2x plus 13 equals 9 is x equals -8.

2x + 5 = 13 2x = 8 2x/2 = 8/2 x=4

2x-3y=13

2x + 1 = 13; 2x = 12; x = 6

x equals 19

3x+5 = 2x+13 3x-2x = 13-5 x = 8

19

answer is 4 7x+19=-2x+55 +2x +2x 9x+19= 0 55 -19 -19 9x = 36 9 9 =4

19-2x=13 19 -13 ------ 6 6/2=3 19-(2)(3)=13 x=3

x + 2y = 27 2x - y = 19 y = 2x - 19 x + 2(2x - 19) = 27 x + 4x - 38 = 27 5x = 65 x = 13 y = 2(13) - 19 y = 7

2x plus 3y

x + 2x + 5 = x +19 3x + 5 = x +19 3x - x = 19 - 5 2x = 14 x = 7

x=(-9)

7

it equals 13X.

-2x+13y=11 13y=2x+11 y=2x/13 + 11/13

(2, 3)

An equation where x equals 3.

X= -8

84

2x+3y=13 3x-y=3 x=2

x-29 = 13+2x x-2x = 13+29 -x = 42 x = -42